Pattern of Cardiovascular Disease among Admitted Patients in Tertiary Care Teaching Hospital - Sharma, Dibya; Kafle, Ram Chandra; Alurkar, Vijay Madhav (Journal of Nepal Health Research Council, 2020)
Background: Cardiovascular diseases are the dominant cause of morbidity and mortality worldwide. In 2008, cardiovascular deaths represented 30% of all global deaths, with more than 80% of deaths in developing countries. There is increase in incidence of hypertension, atherosclerosis, stroke, chronic heart failure and atrial fibrillation. The objective of this study is to find the pattern of cardiovascular diseases among patients admitted in cardiac ward. Methods: A retrospective analysis of records of admitted patients from 1st January 2016 – 30th December 2017 was conducted in Cardiology ward of Manipal Teaching Hospital, Pokhara, Nepal. A total of 2268 patients’ data were taken from the ward register. The data was collected and analyzed with descriptive and inferential statistics using SPSS 18.0 version during the period from 1st June to 30th August 2018. Results: The age ranged between 12 to 95 years with a mean (SD) is 61.23(16.34 years). More than half (51%) of the patients were female gender. Forty-six percentages of the patients were in the age group of 56 – 75 years. More than 1/3rd (35%) were diagnosed with Ischemic heart disease (IHD) followed by hypertension (22.8%) and arrhythmia(13.4%). There was a significant association between age and gender with the pattern of cardiovascular disease. Conclusions: Ischemic heart disease, hypertension and arrhythmia were the major causes of hospitalization. Preventive measures at community and personal level focusing on the risk factors management of ischemic heart disease will alleviate the burden of ischemic heart disease. Keywords: Cardiovascular disease; mortality; pattern; prevalence.